Can we still call OPEC a cartel? - Ali, Dalia; Stroukal, Dominik, 1987-; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
This paper raises the question whether OPEC actually acts like a cartel, given the fact that there were many controversy surrounding the organization due to its coordination failures, which resulted to an oil glut between 2014-2016. Consequently, the oil industry experienced a dramatic decline in oil prices due to the oil surplus. A comparison was made between OPEC's allocated quotas, and its actual oil production to investigate whether the members of the organization adhere to the assigned quota, to achieve highest possible prices.
Vedoucí práce: Dominik Stroukal
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses